DEVELOPING ENGLISH WRITING WORKSHEET OF NARRATIVE TEXT BASED ON SCIENTIFIC APPROACH FOR THE TENTH GRADE STUDENTS OF SMKN 7 MEDAN - Arif Sandi Budiman; Nora Ronita Dewi; Farida Hanim Saragih (Universitas Negeri Medan, 2021)
DEVELOPING ENGLISH WRITING WORKSHEET OF NARRATIVE TEXT BASED ON SCIENTIFIC APPROACH FOR THE TENTH GRADE STUDENTS OF SMKN 7 MEDAN *Arif Sandi Budiman **Nora Ronita Dewi **Farida Hanim Saragih ABSTRACT Sandi, Arif. Registration Number: 2142121001Developing English Writing Worksheet of Narrative Text Based on Scientific Approach for The Tenth Grade Students of SMKN 7 Medan. English Educational Program, Medan State University, 2020. By using scientific approach as a learning material referring to curriculum 2013, the method used in this research is research and development. This research consists of five steps: 1) Gathering data and information, 2) Need analysis, 3) Developing the worksheet, 4) Validating the product, 5) Revising product and presented as a final product. The average score for student worksheet from the mean value from all aspects is 4.7. It could be concluded that the worksheet is categorized as “Very Good” since the position of the mean value was in the interval it is concluded that student worksheet by using scientific approach can be used and distributed as a learning material in English narrative text writing worksheet learning for SMKN 7 Medan grade X. Keywords: Scientific Approach, Teaching, Writing.